2022
DOI: 10.51738/kpolisa2022.19.4r.82sj
|View full text |Cite
|
Sign up to set email alerts
|

Cybercrime in the Republic of Serbia: Prevalence, Situation and Perspectives

Abstract: The year 2022 was marked by anonymous reports of bombings in schools and other important institutions across Serbia, spread via computers. These events have triggered a public debate on whether the authorities responsible for combating cybercrime can adequately respond to such attacks. As the number of internet users increases, so does the number of potential victims of cybercrime and the obligation of states to protect citizens. Recent events have shown the vulnerability of society to high-tech crime and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…Based on previous research on traditional school victimization and cyber-victimization (Bjelajac, Filipovic and Stosic, 2022), the present study found that higher levels of general emotional intelligence were significantly associated with lower rates of cyber-victimization. Our findings in this case are consistent with the assumption that "peer cyber-victimization propensity is to some extent related to emotional maturity or lack thereof" (Stosic and Jankovic, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…Based on previous research on traditional school victimization and cyber-victimization (Bjelajac, Filipovic and Stosic, 2022), the present study found that higher levels of general emotional intelligence were significantly associated with lower rates of cyber-victimization. Our findings in this case are consistent with the assumption that "peer cyber-victimization propensity is to some extent related to emotional maturity or lack thereof" (Stosic and Jankovic, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…They also have a low level of perception that internet crime engagements are believed to be the only source of meeting academic demands and lastly, they have a low level of perception that internet crime engagements are only common among male than the female. This result is in tandem with the findings of [2,3,12] who confirmed the prevalence and involvement of youths in cybercrimes in their respective sample areas including Nigeria. From Table 4, the result of data analysis shows that the majority of respondents perceived that high rate of internet crime among students in the University of Ilorin is as a result of greediness, poverty and social influence.…”
Section: Gendersupporting
confidence: 84%
“…A qualitative research approach was employed by [3] to compare and analyze the normative and institutional framework provided by the Ministry of Internal Affairs on cybercrime to combat the prevalence of cybercrimes in the Republic of Serbia and other European countries. The result of their analysis shows that despite a good normative measure, more efforts still need to be put in place in order to combat cybercrimes in the Republic of Serbia.…”
Section: Internet Crimesmentioning
confidence: 99%
See 2 more Smart Citations